A −40 ​°C–125 ​°C, 1.08 ​ppm/°C, 918 ​nW bandgap voltage reference with segmented curvature compensation. (November 2020) - Yan, Tianzheng; U, Chi-Wa; Law, Man-Kay; Lam, Chi-Seng
Abstract: This paper proposes a precision bandgap voltage reference (BGR) with a segmented curvature compensation technique, demonstrating both small temperature coefficient (TC) and low power consumption. By segmenting the output voltage of a conventional first-order BGR over a wide temperature range and implementing compensation for each segment, the output reference voltage can be systematically aligned to an identical voltage level, effectively reducing the achievable TC. An additional circuit consists of comparators, logic gates, switches and current mirrors is proposed to achieve this compensation scheme, which also optimizes the overall BGR power consumption. Implemented and simulated in a standard 65 ​nm CMOS process, the proposed BGR achieves an average output of 496.17 ​mV and a TC of 1.08 ​ppm/°C from −40 ​°C to 125 ​°C. It consumes a current of 765 ​nA under a 1.2 ​V supply while exhibiting a line regulation of 0.725%/V with VDD from 1.0 to 1.8 ​V ​at 27 ​°C.